ANALISIS GOVERNMENTALITAS DAN REPRODUKSI WACANA DALAM SEJARAH MUNCULNYA PROGRAM KELUARGA BERENCANA DI INDONESIA TAHUN 1970 - Al Farauqi, Mohamad Dziqie Aulia (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract This article tries to apply the concept of governmentality in Michael Foucault's perspective in analyzing the Family Planning discourse which began to be implemented in 1970, precisely under the